Un nuevo modelo sostenible de ocupar el territorio (2021)
The growth of urban, suburban and expansion areas in Colombia has been accelerated and disorderly, due to a series of changes that have altered the rhythm of life of the urban and rural population; From social and natural phenomena that make the process of occupying the territory complex, the research carried out a diagnosis of different urban theories that seek to occupy the territory in a sustainable way. This article is focused on the realization of an urban model of occupation of the territory, under the theory of urban compactness that seeks a sustainable way of occupying the territory based on different postulates such as: urban habitability, social cohesion, relationship between urban space and the built space; generating an occupation model that responds to different types of soil, with a range of possibilities depending on the type of soil.